Concise total synthesis of two marine natural nucleosides: trachycladines A and B - Ding, Haixin; Li, Wei; Ruan, Zhizhong; Yang, Ruchun; Mao, Zhijie; Xiao, Qiang; Wu, Jun (Beilstein Journal of Organic Chemistry, 2014)
We report the first total synthesis of trachycladines A (10 steps, 34.2% overall yield) and B (11 steps, 35.0% overall yield) by using 5-deoxy-1,2,3-tri-O-acetyl-β-D-ribofuranose as the starting material. The critical step was the SnCl4 assisted regio- and steroselective deprotection of perbenzylated 1-O-methyl-5-deoxyribofuranose. The enzyme adenylate deaminase (EC 3.5.4.6) was successfully applied to the chemoenzymatic synthesis of trachycladines B.
Keywords: marine nucleosides; natural products; total synthesis; trachycladines A and B; Vorbrüggen glycosylation